Penerapan Parenting Education Melalui Sosialisasi Terhadap Ibu-Ibu PKK Di Dukuh Manukan Desa Sindon - Annisa Dian Kharisma; Faqih Purnomosidi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Parenting is a learning process in the form of care between parents and chilfren by fulfilling all their needs. Parenting education has big influence on children’s development and to improve children’s character.parents are asked to be active and effective in educating children. Parents also have to control their chilfren more at home and when using cellphones. One of the factors causing children to use cellphones is that childrenbecome disobedient to their parents. The method of this service is lectures and discussions. The method of this service is providing explanation and understanding and tips on how to educate and guide children in Dukuh Manukan. The conclusion from the dedication carrid out bt the author is that parenting education is very effective in educating and guiding children so that children become closer to their parents.